Effects of Plyometric Jump Training on Balance Performance in Healthy Participants: A Systematic Review With Meta-Analysis - Ramachandran, Akhilesh Kumar; Singh, Utkarsh; Ramirez-Campillo, Rodrigo; Clemente, Filipe Manuel; Afonso, José; Granacher, Urs (Frontiers in Physiology, 2021)
Objective: To systematically review and synthetize evidence from randomized and non-randomized controlled trials regarding the effects of PJT on measures of balance in apparently healthy participants. Methods: Systematic literature searches were performed in the electronic databases PubMed, Web of Science, and SCOPUS. A PICOS approach was applied to define inclusion criteria, i) apparently healthy participants, with no restrictions on their fitness level, sex, or age, ii) a PJT program, iii) active controls (any sport-related activity) or specific active controls (a specific exercise type such as balance training), iv) assessment of dynamic, static balance pre- and post-PJT, v) randomized controlled trials and controlled trials. The methodological quality of studies was assessed using the Physiotherapy Evidence Database (PEDro) scale. This meta-analysis was computed using the inverse variance random-effects model. The significance level was set at p<0.05. Results: The initial search retrieved 8,251 plus 23 records identified through other sources. Forty-two articles met our inclusion criteria for qualitative and 38 for quantitative analysis (1,806 participants [990 males, 816 females], age range 9-63 years). PJT interventions lasted between 4 to 36 weeks. The median PEDro score was 6 and no study had low methodological quality (≤3). The analysis revealed significant small effects of PJT on overall (dynamic and static) balance (ES = 0.46; 95% CI = 0.32 to 0.61; p< 0.001), dynamic (e.g., Y-balance test) balance (ES = 0.50; 95% CI = 0.30 to 0.71; p<0.001), and static (e.g., flamingo balance test) balance (ES = 0.49; 95% CI = 0.31 to 0.67; p<0.001). The moderator analyses revealed that sex and/or age did not moderate balance performance outcomes. When PJT was compared to specific active controls (i.e., participants undergoing balance training, whole body vibration training, resistance training), both PJT and alternative training methods showed similar effects on overall (dynamic and static) balance (p=0.534). Specifically, when PJT was compared to balance training, both training types showed similar effects on overall (dynamic and static) balance (p=0.514). Conclusions: Compared to active controls, PJT showed small effects on overall balance, dynamic and static balance. Additionally, PJT produced similar balance improvements compared to other training types (i.e., balance training).